Opti OPTIMALISASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN: Studi Kasus di Kecamatan Karawaci Kota Tangerang - Rachmat Gustiana; MD Sukamto (iLearning Journal Center, 2019)
Tangerang Mayor Regulation No. 13 of 2016 concerning Integrated District Administrative Services (PATEN) in Tangerang City became the legal umbrella for the implementation of PATENT in all Sub-Districts in the Tangerang City area, including Karawaci District. With the PATENT, customers will not need to go to the Tangerang City Government Center, but simply submit administrative requirements to the sub-district officer and subsequent arrangements will be made by the sub-district officials. So that the service is completed in the sub-district. While for the types of small-scale licenses can be submitted entirely to the sub-district. The research method used is a qualitative method. This method is used to answer research problems, namely how is the implementation of prime public services referring to PATENT based on Minister of Home Affairs Number 4 of 2010 and Indicator of Community Satisfaction Survey based on Minister of Administrative Reform and Bureaucratic Reform Number 16 of 2014